Professional competencies' profile for the Internal Medicine specialist based on integrative medicine - Luis Aníbal Alonso Betancourt; Edilio Silva Velasco; Juan Carlos Baster Moro; Mayelín Cruz Batista (Medisur)
Foundation: the postgraduate academic training of human resources in health aims at consolidating professional competencies in their care, teaching, educational and administrative performances, innovation and creation, which is recognized with an academic title or a scientific degree. Objective: to propose the professional competencies' profile for the Internal Medicine specialist based on integrative medicine. Methods: A pre-experimental cross-sectional research was carried out in an intentional non-probabilistic sample of 21 Internal Medicine residents from the Vladimir Ilich Lenin University General Hospital in Holguín. The methods of observation, analysis, synthesis, document review, promotion exams and the Chi-square test were used to verify the transformations achieved with the application of the proposed competency profile. Results: A profile of professional competencies for Internal Medicine specialists was provided based on integrative medicine as a novel aspect and the transformations achieved with its application in the professional performance of this specialty residents in the fulfillment of their duties in the workplace. Conclusions: Training professional competencies in Internal Medicine residents from the integrative medicine approach contributes to develop a more comprehensive vision in the application of diagnostic and therapeutic protocols for the solution of health problems in this service from a contemporary medical worldview.